Pengaruh fluktuasi harga bawang merah terhadap perilaku konsumsi rumah tangga dan integrasi pasar di kota cirebon - Iksan; Jaka Sulaksana; Dinar (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Shallots are one of the strategic horticultural commodities in Indonesia with high economic value and significant influence on household consumption expenditure. Price fluctuations frequently occur due to changes in production, seasonal factors, market demand, and distribution systems. This study aims to analyze the effect of shallot price fluctuations on household consumption behavior in Cirebon City and to examine market integration between Cirebon City and Brebes Regency as the main production center. The study employed a survey method involving 34 household respondents selected through purposive sampling. Primary data were collected through questionnaires and interviews, while secondary data consisted of monthly shallot price data from January to December 2023. Data analysis included descriptive statistics, simple linear regression, Pearson correlation, cointegration analysis, and Granger causality tests. The results showed that shallot prices fluctuated significantly during 2023, with the highest price recorded in April at IDR 28,350/kg and the lowest in September at IDR 14,350/kg. Regression analysis indicated that price fluctuations had a significant negative effect on household consumption behavior. Pearson correlation analysis produced a coefficient of -0.61, indicating a strong negative relationship between price and consumption. Furthermore, cointegration and Granger causality analyses revealed that shallot prices in Brebes significantly influenced prices in Cirebon, while the opposite relationship was not observed. These findings indicate that household consumption is responsive to price changes and that market integration exists, although market efficiency remains limited.